Philosophy of nature - Feyerabend, Paul 1924-1994; Heit, Helmut; Oberheim, Eric; Lotter, Dorothea (Malden, Massachusetts Polity, 2016)
Philosopher, physicist, and anarchist Paul Feyerabend was one of the most unconventional scholars of his time. His book Against Method has become a modern classic.
Includes bibliographical references and index.
Keywords: Philosophy of nature